Mathematical models of functioning of enterprises of technical service of career dump trucks (ADVANCES IN MECHANICAL ENGINEERING AND TRANSPORT, 2019)
Improvement of quality of technical service, labor and cost savings is possible in the process of solution-finding for determination of usefulness of specialization in open pit trucks technical service operations within the conditions of the enterprises of a region. The solution can be found from improving one of the existing models of car service centers functioning with the use of the change of operations that enter transportation costs. It can be obtained by factoring out transportation costs in the objective function of planning, design, siting and specialization of auto industry enterprises.The areas of research are: determination of optimal layout design and specialization of open pit trucks technical service centers, determination of the optimal plan of specialization of existing mining and transport workshops or open pit trucks technical service centers, determination of optimal layout design and specialization of open pit trucks technical service centers that are being built or already exist.The limitations of the mathematical economic models are: open pit trucks owners’ demand for handling all types of operations must be fully satisfied, the number of open pit trucks arriving over the service center for maintenance should not exceed the maximum capacity of the center, the design capacity of a service center must not exceed its maximum output for any type of handling operation, the number of open pit trucks should be greater than or equal to zero, the limit of use of production facilities, the limit of use of labor.The mathematical economic models of operation, siting and specialization of open pit trucks technical service enterprises are presented which, in contrast to similar models of car service enterprises operation, allows to save technical service costs considering open pit trucks maintenance at their working area and its repair at specialized enterprises.Keywords: open-pit dump truck, major repairs, production costs, economical and mathematical design.